2019
DOI: 10.1093/neuros/nyz229
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes and Dose Rate Effects Following Gamma Knife Stereotactic Radiosurgery for Vestibular Schwannomas

Abstract: BACKGROUNDGamma Knife radiosurgery (GKRS; Elekta AB) remains a well-established treatment modality for vestibular schwannomas. Despite highly effective tumor control, further research is needed toward optimizing long-term functional outcomes. Whereas dose-rate effects may impact post-treatment toxicities given tissue dose-response relationships, potential effects remain largely unexplored.OBJECTIVETo evaluate treatment outcomes and potential dose-rate effects following definitive GKRS for vestibular schwannoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…When it comes to SRS, the tumor control rate is comparable to conventional microsurgery 21 . It was able to maintain serviceable hearing at four years in 72.2% of the total patient in a study 22 . However, in a study that observed for a longer time, only 23% of the patient's hearing was preserved following ten years of treatment 23 .…”
Section: Discussionmentioning
confidence: 89%
“…When it comes to SRS, the tumor control rate is comparable to conventional microsurgery 21 . It was able to maintain serviceable hearing at four years in 72.2% of the total patient in a study 22 . However, in a study that observed for a longer time, only 23% of the patient's hearing was preserved following ten years of treatment 23 .…”
Section: Discussionmentioning
confidence: 89%
“…Overall, the progression free survival (PFS) after GammaKnife SRS is approximately 84–94% [ 197 , 198 , 199 ]. However, some studies have shown that larger VS tumors and those from NF2 patients have an overall lower rate of tumor control than those published for sporadic tumors that are small and medium sized [ 34 , 35 , 200 ].…”
Section: Radiobiology and Radiation Resistance In Vestibular Schwannomamentioning
confidence: 99%
“…The 20-Gy doses were delivered at rates of 1.5-2.5 Gy/min, whereas the 10-Gy dose was delivered at a much faster rate of 6.4 Gy/min, which, in turn, is related to the respective use of lower (90-320 kV) and higher (6 MeV) energies of radiation. More recently, in a study 25 involving irradiation of the vestibular nerve with a dose of approximately 17 Gy, the dose rate was found to be an important variable in irradiating nervous tissue since deleterious effects-i.e., facial nerve dysfunction and hearing loss-were found to be greater when irradiating at dose rates higher, but not lower, than 2.7 Gy/min. This radiation-induced toxicity to nervous tissue found at higher dose rates would be consistent with a dose of 20 Gy being effective for treating SCI when delivered at a lower, but not a higher, dose rate, as has been observed.…”
Section: Fig 2 Cmentioning
confidence: 99%